Individualist-collectivist profiles in secondary school: an exploratory study of trait emotional intelligence and academic achievement - Costa, Ana (2024)
An individualist (I) or collectivist (C) cultural orientation affects individuals’ attitudes, behaviours and values. This study aimed to identify the first-year secondary-school students’ I–C profiles and explore their implications for students’ trait emotional intelligence (EI), emotions towards school and academic achievement (GPA) throughout the 3-year secondary-school cycle. A total of 222 secondary-school students (58.6% females; Mage = 15.4; SD =.63 in the 10th grade) were enrolled in a longitudinal study. The cluster analysis identified three distinct I–C profiles: high individualist-low collectivist students, low individualistic-midlevel collectivist students and high individualist–high collectivist students. The results revealed significant differences between the I–C profiles regarding students’ trait EI, emotions towards school and GPA throughout secondary school, in particular favouring the high individualist–high collectivist profile. These findings are discussed based on the practical implications for students’ outcomes in the current secondary school system.